Towards rational design of RAD51-targeting prodrugs: platinumIV–artesunate conjugates with enhanced cytotoxicity against BRCA-proficient ovarian and breast cancer cells. Issue 83 (19th September 2018) - Zhang, Shuren; Yuan, Hao; Guo, Yan; Wang, Kun; Wang, Xiaoyong; Guo, Zijian
Abstract : Pt IV –Artesunate prodrugs target the homologous recombination protein RAD51 and exhibit higher cytotoxicity against BRCA-proficient ovarian and breast cancer cells than cisplatin. Abstract : Two Pt IV –artesunate anticancer prodrugs that target RAD51, a crucial protein in homologous recombination mediating the sensitivity of cancer cells to DNA-damaging agents, were designed; their cytotoxicities against BRCA-proficient ovarian and breast cancer cells are significantly higher than those of cisplatin.